INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM KELUARGA - Nur Qomari (JIP: Jurnal Ilmu Pendidikan, 2025)
Education is a shared responsibility between the government, society and families, so that based on this responsibility, education in Indonesia is organised through three channels, namely formal, non-formal and informal education. Informal educational activities carried out by families and the community take the form of independent learning activities. The family, as the first centre of Islamic education, is the initial phase, the basis, and the foundation that is crucial to the continuity and success of further education, because education within the family is a natural centre of education that takes place in a natural manner compared to other centres of education. Parents, as the people most responsible for their children's education, have an obligation to educate their children in accordance with the mandate given to them by Allah SWT. There are three methods that can be used to internalise Islamic educational values in the family, including teaching, exemplary behaviour, guidance and habit formation. Meanwhile, the Islamic educational values internalised in the family are a. Ilahiyah values. Ilahiyah values are values that arise from a belief in supernatural guidance or God. These values are divided into the values of faith or monotheism and morals, the values of worship, and the values of muamalah. b. Human values. Human values are values that arise or are formed from the culture and conditions of the surrounding community, both individuals and groups. Human values are divided into ethical, social, and aesthetic values.